Valuing, growing and retaining Pacific leaders and teachers (Kairaranga, 2023)
The Ministry of Education document Action Plan for Pacific Education 2020-2030 is a government commitment to transform outcomes for Pacific learners and their families. Key Shift 5 of this Action Plan focuses on valuing, growing, and retaining “teachers, leaders, and educational professionals with diverse Pacific heritages” (Ministry of Education, 2020a, p. 38). This professional inquiry explored what Key Shift 5 looks like within the Resource Teaching service. A literature review examined ethnic minority leadership in education, specifically looking at the enablers and barriers. The Pacific research method, talanoa, was used to give voice to the lived experiences of four ex-Resource Teachers: Learning and Behaviour (RTLB). Findings from this inquiry acknowledge the misrepresentation of Pacific in decision making spaces and highlight the benefits and advantages Pacific RTLB bring to their roles. The importance of support from senior management was indicated by all participants as a key factor in valuing, growing, and retaining “teachers, leaders, and educational professionals with diverse Pacific heritages”.